Randomized Comparative Study of the Effects of Treatment with Once-Daily, Niacin Extended-Release/Lovastatin and with Simvastatin on Lipid Profile and Fibrinolytic Parameters in Taiwan - Tsung-Hsien Lin; Wen-Chol Voon; Hsueh-Wei Yen; Chih-Hsin Huang; Ho-Ming Su; Wen-Ter Lai; Sheng-Hsiung Sheu (Kaohsiung Journal of Medical Sciences, 2006)
Hyperlipidemia can be effectively treated either with niacin or HMG-CoA reductase inhibitor (statin), or a combination of both. Few reports showed the effects of the combination regimen with niacin and statin on hemostatic functions. We conducted a single-center, double-blind, double-dummy, randomized, two-arm study to assess the effects of the niacin extended-release/lovastatin therapy in a fixed-dose formulation and of simvastatin on lipid lowering and two fibrinolytic parameters, fibrinogen and d-dimer. All patients were enrolled according to NCEP-ATP III guidelines and underwent a placebo run-in period of 4 weeks before being randomized to either niacin extended-release/lovastatin tablets (500/20 mg) once daily (n = 36) or simvastatin capsule (20 mg) once daily (n = 34). After 16 weeks of treatment, both groups of patients showed significantly reduced low-density lipoprotein cholesterol and total cholesterol (LDL-C, p < 0.001 and < 0.001, respectively, p = 0.159 between the groups; TC, p < 0.001 and < 0.001, respectively, p = 0.018 between the groups). Both drugs were well tolerated. Only in the group treated with niacin extended-release/lovastatin was fibrinogen concentration significantly reduced after treatment (2.48 ± 0.65 to 1.99 ± 0.62 g/L, p = 0.008). No difference was found with d-dimer in either group. This study shows that both niacin extended-release/ lovastatin and simvastatin are effective and well-tolerated lipid-lowering drugs in Taiwanese patients with dyslipidemia. A combinational treatment with niacin extended-release/lovastatin may provide additional benefit in fibrinolysis.